Protective effects of bitter almond kernel oil on some biochemical parameters in brain tissue of diabetic - Demir, Ersin; Keser, Serhat; Yilmaz, Okkes (Ejmanager Llc, 2013)
Aim: In this study, we aimed to determine possible protective effects of the bitter almond kernel oil extract on the lipid-soluble vitamins, cholesterol, GSH, total protein, MDA and fatty acid levels of brain tissue in the streptozotocin-induced diabetic Wistar rats. Method: The lipid-soluble vitamins, cholesterol and other sterol levels were measured by HPLC, the fatty acid levels were measured by GC, MDA, GSH and total protein levels were measured by UVVis spectrophotometer. Results: Whereas the alpha-tocopherol and GSH levels were decreased in the diabetes (D) group, these parameters were protected in the diabetes + almond oil (D+ AO) group when compared to control (C) group. The total protein and MDA levels were increased in the D group, but their levels were not changed in the D+ AO group. The palmitic acid and stearic acid levels were increased in the D and D+ AO groups. The arachidonic acid and docosahexaenoic acid levels were increased in the D group, but these fatty acid levels were not changed in the D+ AO group when compared to the C group. In conclusion, according to our results, bitter almond oil was shown that some positive effects on the biochemical parameters of brain tissue in the diabetic rats. Conclusion: This oil was protected or prevented the GSH and MDA levels in bitter almond oil extract given group, and these values were closed to control group values. (C) 2013 GESDAV
Keywords: Bitter almond; MDA; diabetes; cholesterol; GSH; brain